O fazer artístico como catálise: experiências do corpo e da dança - Camargo, Mariana Vaz de (2008)
This research (The artistic act as catalysis: experiences in the body and dance) reflects upon the intensive dimension of the artistic act. It seems to me that art (the creative state) can catalyze and intensify potential for change, open up areas of movement and promote new connections and potential . The sensitivity promoted by this act should be different from that organizing our everyday experience; through this reorganization, transmutation or metamorphoses comes its political potential. Catalyze: a term borrowed from Chemistry imbued with a special meaning. Existential-poetic catalysis is how Guattari denominates the process of the search for paths to singular new existential territories, not serialized. To give shape to my reflections I interviewed the seven performers-creators of Cia. Nova Dança 4, a dance-theatre company from São Paulo. I was interested in grasping through the traces of the pulsating nature, the collective movements of the appropriation and invention of life which favour the production of singular existences. Why is art produced and consumed ? What ecstasy is this, that of poetry? I found two responses: the Russian psychologist Vygotsky s (art as a social technique of feelings that operates catharsis) and Deleuze and Guattari s (aesthetics in the relationship between forms and forces that can catalyze the invention of new existential territories). Because of the chosen theoretical framework it is not possible to talk about art without talking about the body and the need to return to it in that which is most singular: the porous body which is affected by encounters and partings in the world. Perhaps some experiences in contemporary dance can invent and construct bodies open to other forces and intensities Body without Organs. Elements that emerged during the construction of this framework led me to reflections of a more sociological nature: the institutional aspects of dance, formation of artistic groups and being an artist today . I also review the history of dance in the West and the principal elements of Contact Improvisation (in dialogue with Michel Foucault s reflections on power/body). Finally, I recover Vygotsky s conception of catharsis with a view to broadening the notion of catalysis. I understand that the discussion of the definition and use of these two terms, as well as their reorganization, can increase their power of creation-action (especially in the draw of the performing arts in question)